THE INFLUENCE OF PERCEPTIONS AND LIFESTYLE OF COLLEGE STUDENTS ON INVESTMENT INTEREST IN ISLAMIC MUTUAL FUNDS DURING THE COVID-19 PANDEMIC - Annisa Sriayuning Megawati; Moh. Djemdjem Djamaludin (Journal of Child, Family, and Consumer Studies, 2023)
The Covid-19 pandemic has an impact on the economy which is getting worse, so investment is one way out that needs attention as an alternative source of income from the returns generated. This study aims to analyze the influence of perceptions and lifestyles of students on interest in investing in Islamic mutual funds during the Covid19 pandemic. This study uses a cross sectional study design, with the SEM-PLS analysis method. The population of this study were undergraduate students throughout Indonesia. Respondents were selected by voluntary sampling with a total of 100 respondents. Muslim students have better perceptions and higher investment interest in Islamic mutual funds, and have a hedonic lifestyle compared to non-Muslim students. Then, students with good perceptions of Islamic mutual funds and having a frugal lifestyle have an effect on increasing interest in Islamic mutual fund investment. Students are expected to increase their interest in investing in Islamic mutual funds by changing their previously hedonic lifestyle to a frugal lifestyle, this can be done by starting to make financial plans for the long, medium and short term and prioritizing needs to be able to meet financial goals in the future.